A Tale from TGF-β Superfamily for Thymus Ontogeny and Function - Jurberg, Arnon Dias; Vasconcelos-Fontes, Larissa; Cotta-de-Almeida, Vinícius (Frontiers in Immunology, 2015)
Multiple signaling pathways control every aspect of cell behavior, organ formation and tissue homeostasis throughout the lifespan of any individual. This review takes an ontogenetic view focused on the large superfamily of TGF-β/BMP ligands to address thymus morphogenesis and function in T cell differentiation. Recent findings on a role of GDF11 for reversing aging-related phenotypes are also discussed.